A Prospective Study of Family Satisfaction Changes After Tracheostomy Placement in Trauma Patients. Issue 6 (June 2021) - Trust, Marc D.; Lara, Sabino; Hecht, Jonathan; Teixeira, Pedro G.; Coopwood, Ben; Aydelotte, Jayson; Cardenas, Tatiana C. P.; Guerra, Erin; Ali, Sadia; Brown, Carlos V. R.
Background: Tracheostomy is a commonly performed procedure in surgical intensive care units. Although the indications and benefits of this procedure are well known, little has been studied in the adult surgical/trauma population about patient family satisfaction after tracheostomy placement. Materials and Methods: We performed a prospective study at our academic level I trauma center from 2015-2016 in patients who underwent elective tracheostomy. Family members were asked to complete an eight-point questionnaire using a forced Likert scale of graded responses. Questionnaires were administered prior to tracheostomy and again at 24-and 72-hour post-tracheostomy placement. Responses were compared using univariate analysis. Results: A total of 26 family members completed all 3 surveys. Family members believed loved ones appeared more comfortable, were more interactive, and were better progressing clinically. After 72 hours, family members felt less anxiety. There was no difference in perceptions of patient distress, ability to provide support, or their worry about scars, or comfort in visiting them. Discussion: Family members believed tracheostomies provided greater patient comfort, increased interactive abilities, better progress in their care, and experienced less anxiety after placement. Family satisfaction may therefore be an additional benefit in support of earlier tracheostomy.